So Long and Thanks for All the Fish: Overexploitation of the Regionally Endemic Galapagos Grouper Mycteroperca olfax (Jenyns, 1840) - Usseglio, Paolo (PLoS One, 2016)
The regionally endemic Galapagos Grouper, locally known as bacalao, is one of the most highly prized finfish species within the Galapagos Marine Reserve (GMR). Concerns of overfishing, coupled with a lack of fishing regulations aimed at this species raises concerns about the current population health. We assessed changes in population health over a 30-year period using three simple indicators: (1) percentage of fish below reproductive size (L(m)); (2) percentage of fish within the optimum length interval (L(opt)); and (3) percentage of mega-spawners in the catch. Over the assessed period, none of the indicators reached values associated with healthy populations, with all indicators declining over time. Furthermore, the most recent landings data show that the vast majority of the bacalao caught (95.7%,) were below L(m), the number of fish within the L(opt) interval was extremely low (4.7%), and there were virtually no mega-spawners (0.2%). Bacalao fully recruit to the fishery 15 cm below the size at which 50% of the population matures. The Spawning Potential Ratio is currently 5% of potential unfished fecundity, strongly suggesting severe overfishing. Our results suggest the need for bacalao-specific management regulations that should include minimum (65 cm TL) and maximum (78 cm TL) landing sizes, slot limits (64–78 cm TL), as well as a closed season during spawning from October to January. It is recognized that these regulations are harsh and will certainly have negative impacts on the livelihoods of fishers in the short term, however, continued inaction will likely result in a collapse of this economically and culturally valuable species. Alternative sources of income should be developed in parallel with the establishment of fishing regulations to limit the socio-economic disruption to the fishing community during the transition to a more sustainable management regime.